A decision support system for IMS selection based on fuzzy VIKOR method. (2015) - ,; Kumar, Darshan
Intelligent manufacturing system (IMS) presents system with autonomous ability to adapt to unexpected changes. In order to succeed in this ever so demanding, fast pace business environment, managers need integrated and IMS capable of supporting them throughout the decision-making lifecycle. Therefore, it is worthwhile to invest on making appropriate decisions on IMS selection. The selecting process mainly involves evaluation of different alternatives based on different criteria. This process is essentially considered as a multiple criteria decision-making (MCDM) problem which is affected by different tangible and intangible criteria including price, quality, performance, lead-time, efficiency, etc. This paper presents a model based on VIKOR method to select an appropriate IMS. Based on the concept of fuzzy logic and the VIKOR method, the proposed fuzzy VIKOR method has been developed to provide a rational and systematic process. The proposed method can be used to find a best solution to resolve a fuzzy MCDM problem and to specify the preferred solution for any decision problem in real organisational set up.